2020
DOI: 10.1016/j.envpol.2019.113516
|View full text |Cite
|
Sign up to set email alerts
|

The mechanism of root growth inhibition by the endocrine disruptor bisphenol A (BPA)

Abstract: Bisphenol A (BPA) is a harmful environmental contaminant acting as an endocrine disruptor in animals, but it also affects growth and development in plants. Here, we have elucidated the functional mechanism of root growth inhibition by BPA in Arabidopsis thaliana using mutants, reporter lines and a pharmacological approach. In response to 10 ppm BPA, fresh weight and main root length were reduced, while auxin levels increased. BPA inhibited root growth by reducing root cell length in the elongation zone by supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 89 publications
(118 reference statements)
1
7
0
Order By: Relevance
“…Plants roots are the main organs directly exposed to dinotefuran stress, and then, the growth of root sensitively responds to the changes in the external environment. , Dinotefuran was reported to be relatively stable in the soil environment, with a long half-life ranging from 50 to 100 days. The residues of neonicotinoids have been detected in various soils, with concentrations in the range of parts per billion (μg/kg) to parts per million (mg/kg). , Previous results have shown that dinotefuran induces an excess generation of ROS at 1.0 and 2.0 mg/kg, resulting in significant changes in the antioxidant enzyme activities in a dose- and time-dependent manner .…”
Section: Resultsmentioning
confidence: 99%
“…Plants roots are the main organs directly exposed to dinotefuran stress, and then, the growth of root sensitively responds to the changes in the external environment. , Dinotefuran was reported to be relatively stable in the soil environment, with a long half-life ranging from 50 to 100 days. The residues of neonicotinoids have been detected in various soils, with concentrations in the range of parts per billion (μg/kg) to parts per million (mg/kg). , Previous results have shown that dinotefuran induces an excess generation of ROS at 1.0 and 2.0 mg/kg, resulting in significant changes in the antioxidant enzyme activities in a dose- and time-dependent manner .…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, it is likely that phloretin-induced up-regulation of PIN1 , PIN3 and PIN7 genes complements local auxin biosynthesis generating more robust auxin maxima in root tips and induces increased auxin accumulation in lateral parts of the root tips, as visualized in Arabidopsis transgenic line DR5rev::GFP. The phytotoxicity of bisphenol A ( Bahmani et al, 2020 ) and weisiensin B ( Li et al, 2019 ) was also based on the increased expression of PIN1, PIN3 or PIN7 in roots.…”
Section: Discussionmentioning
confidence: 99%
“…AUX1/LAX proteins are responsible for the auxin intake ( Swarup et al, 2001 ), while PINs show asymmetric localization on cell membranes in certain cell types, correlated with known acropetal and basipetal directions of auxin flow ( Vieten et al, 2005 ; Michniewicz et al, 2007 ; Figure 1C ). All auxin carriers act synergistically mediating the plasticity of the root system architecture when they adapt to various environmental stimuli ( Sun et al, 2010 ; Yuan et al, 2013 ; Li et al, 2015 ; Yuan and Huang, 2016 ; Bahmani et al, 2020 ) or respond to soil allelochemicals ( Zhang et al, 2018 ; Li et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although plants can absorb and metabolize BPA, at the same time BPA could deteriorate their cellular/physiological status ( Zhang et al., 2017 ). It has been shown that experimentally applied concentrations of BPA (mg/L) negatively affected the growth of many important crops, e.g., soybean ( Qui et al., 2013 ; Zhang et al., 2016 ; Jiao et al., 2017 ; Li X. et al., 2018 ; Zhang et al., 2018 ; Xiao et al., 2019 ), pea ( Adamakis et al., 2013 ), wheat ( Adamakis et al., 2019 ), maize ( Stavropoulou et al., 2018 ), rice ( Ali et al., 2016 ), cucumber ( Li Y. T. et al., 2018 ) and onion ( Adamakis et al., 2019 ); also of non-cultivated plants such as the Cephalonian fir ( Adamakis et al., 2016 ) and the model plant Arabidopsis thaliana ( Pan et al., 2013 ; Tian et al., 2014 ; Frejd et al., 2016 ; Ali et al., 2017 ; Rapala et al., 2017 ; Bahmani et al., 2020 ). Growth reduction effects have interestingly been found to occur also after environmentally relevant concentrations (μg/L) applied on cultivated crops, e.g., cabbage and tomato ( Staples et al., 2010 ), native plants such as oat ( Staples et al., 2010 ) and seagrasses ( Adamakis et al., 2018 ; Malea et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…BPA-derived growth defects have been linked to either cytoskeletal derangement ( Adamakis et al., 2013 ; Adamakis et al., 2016 ; Adamakis et al., 2018 ; Stavropoulou et al., 2018 ; Adamakis et al., 2019 ), hormonal imbalance ( Frejd et al., 2016 ; Li X. et al., 2018 ; Bahmani et al., 2020 ), deterioration of the photosynthetic machinery ( Jiao et al., 2017 ; Kim et al., 2018 ; Li Y. T. et al., 2018 ) or ROS production ( Wang et al., 2015 ; Ali et al., 2016 ; Zhang et al., 2018 ; Xiao et al., 2019 ). It could therefore be concluded that BPA effects in plants are pleiotropic ( Xiao et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%